Lactylation in post-stroke fatigue: linking metabolic dysregulation to neuroinflammation - Hu, Zekai; Sun, Qingui; Liu, Xinhao; Wang, Jinyan; Jin, Xieyun; Hu, Jun (Frontiers in Neuroscience, 2026)
Lactylation, a recently identified post-translational modification derived from lactate, has emerged as a key immunometabolic regulator in neurological disorders. In the context of ischemic stroke, abnormal lactate accumulation not only reflects energy metabolism dysfunction but also drives protein lactylation, which dynamically influences neuronal survival, glial activation, and neuroinflammatory cascades. Increasing evidence indicates that lactylation modulates transcriptional programs of microglia and astrocytes, amplifying inflammatory responses through histone modifications and metabolic enzyme regulation. These processes contribute critically to the onset and persistence of post-stroke fatigue (PSF), a debilitating complication that impairs recovery and quality of life in stroke survivors. This review integrates recent findings on lactylation-mediated regulation of immune and inflammatory pathways, with a particular focus on its effects on apoptosis-related signaling, mitochondrial dysfunction, and cytokine production. Furthermore, we highlight lactylation-related enzymes, including p300 and HDAC3, as potential therapeutic targets, and discuss emerging biomarkers for monitoring lactylation dynamics in stroke patients. By framing lactylation as a metabolic–epigenetic bridge connecting cellular energy states with immune responses, this article provides new insights into the immunopathogenesis of PSF and identifies promising directions for translational intervention.